A Profitability and Risk Decomposition Analysis of the Open Economy Insurance Sector - Zdeněk Zmeškal; Dana Dluhošová; Karolina Lisztwanová; Iveta Ratmanová (Risks)
The objective of this paper is to analyse profitability and risk through the return on equity (ROE) measure of the open economy insurance sector in a non-stable economic period with an economic shock chain, during the years 2018–2022, characterised by an overheating economy, the Covid pandemic, the war in Ukraine, and a high-inflation wave. The ROE pyramid decomposition structure is proposed, along with the detailed CARAMEL version. A static and risk (dynamic) decomposition deviation analysis is used. The yearly non-stable drivers of insurance sector profitability deviation were confirmed. Despite this, the most influential were the earnings ratio deviations in either increasing or decreasing ROE alternatives. Solvency positively influenced the ROE deviation. It turned out that earnings and asset quality enormously increase the risk of the insurance sector. Conversely, risk is decreased mainly by liquidity and management. Simultaneously, significant, influential factors were identified. The results can serve as a background for carrying out operations, strategic analysis, and decision-making.